A 400-ka tephrochronological framework for Central America from Lake Petén Itzá (Guatemala) sediments. (15th October 2016) - Kutterolf, S.; Schindlbeck, J.C.; Anselmetti, F.S.; Ariztegui, D.; Brenner, M.; Curtis, J.; Schmid, D.; Hodell, D.A.; Mueller, A.; Pérez, L.; Pérez, W.; Schwalb, A.; et al.
Abstract: Lake Petén Itzá, northern Guatemala, lies within a hydrologically closed basin in the south-central area of the Yucatán Peninsula, and was drilled under the auspices of the International Continental Scientific Drilling Program (ICDP) in 2006. At 16°55′N latitude, the lake is ideally located for study of past climate and environmental conditions in the Neotropical lowlands. Because of its great depth (>160 m), Lake Petén Itzá has a record of continuous sediment accumulation that extends well into the late Pleistocene. A key obstacle to obtaining long climate records from the region is the difficulty of establishing a robust chronology beyond ∼40 ka, the limit of 14 C dating. Tephra layers within the Lake Petén Itzá sediments, however, enable development of age/depth relations beyond 40 ka. Ash beds from large-magnitude, Pleistocene-to-Holocene silicic eruptions of caldera volcanoes along the Central American Volcanic Arc (CAVA) were found throughout drill cores collected from Lake Petén Itzá. These ash beds were used to establish a robust chronology extending back 400 ka. We used major- and trace-element glass composition to establish 12 well-constrained correlations between the lacustrine tephra layers in Lake Petén Itzá sediments and dated deposits at the CAVA source volcanoes, and with their marine equivalents in eastern Pacific Ocean sediments. The data also enabled revision of eight previous determinations of erupted volumes and masses, and initial estimates for another four eruptions, as well as the designation of source areas for 14 previously unknown eruptions. The new and revised sedimentation rates for the older sediment successions identify the interglacial of MIS5a between 84 and 72 ka, followed by a stadial between 72 and 59 ka that corresponds to MIS4. We modified the age models for the Lake Petén Itzá sediment sequences, extended the paleoclimate and paleoecological record for this Neotropical region to ∼400 ka, and determined the magnitude and timing of CAVA eruptions. Highlights: Dating 400 ka paleoclimate record of Neotropics. Revision and new eruptive volumes for large Central American eruptions. Age models for Petén Itzá sediments. Linking lacustrine ash inventory to eruptions from Central America and Mexico.